Gambaran Pemahaman Mahasiswa MIK STIKes Santa Elisabeth Medan Mengenai Penyajian Data dalam Bentuk Diagram, Tabular dan Grafikal - Febina Sembiring; Noni Simbolon; Refina Br Tarigan; Anastasya Br Sinuraya (Yayasan Literasi Sains Indonesia, 2024)
Presenting data in the form of diagrams is an effective visualization method for conveying complex information in a clear and easy to understand way. Diagrams, such as bar charts, pie charts, and line charts, make data analysis easier by presenting data between variables, data distribution, and developing trends. This research aims to see the understanding of MIK STIKes Santa Elisabeth Medan students regarding the presentation of diagrammatic, tabular and graphical data. This research uses a descriptive design with a quantitative approach. The sample in this study amounted to 30 people. In this research, researchers collected data using a questionnaire. This research was conducted in July 2024. Data was analyzed univariably. The research results showed that there were 12 (40%) students who had a very good understanding, 11 (36.67) had sufficient understanding, 7 (23.33) lacked understanding. In this case, practice is increased to better understand. After MIK STIKes Santa Elisabeth students understand the presentation of diagram, tabular and graphical data, MIK STIKes Santa Elisabeth students can practice the presentation of diagram, tabular and graphical data correctly and precisely. The presentation of diagram, tabular and graphical data can increase the knowledge of STIKes Santa Elisabeth students more widely about the presentation of diagram, tabular and graphical data. So that STIKes Santa Elisabeth students become competent and qualified students.